Kualitas Hidup Pasien dengan Diabetes Melitus Tipe 2 - Marsitha, Lisa; Syarif, Hilman; Sofia, Sofia (Journal of Telenursing (JOTING), 2023)
This study aims to determine the quality of life of type 2 diabetes mellitus (T2DM) patients in the outpatient department of the General Hospital in Aceh Province. The research method used a cross sectional study approach with data collection using questionnaires, namely sociodemographic questionnaires and World Health Organization Quality of Life (WHOQOL)-BREF questionnaires. The results showed that the quality of life of outpatients with type 2 diabetes mellitus in the physical health domain was in the less category (54.2%) and was in the good category for three other domains, namely the psychological domain (63.3%), the social relationship domain (52.8%) and the environmental domain (33.6%). Type 2 diabetes mellitus affects the quality of life of the sufferer. Measuring the quality of life of type 2 diabetes mellitus patients is important because it can identify individuals with poor quality of life and various predictors of quality of life. Keywords: Type 2 Diabetes Mellitus, Quality of Life, WHOQOL-BREF